Discordant architectural and cytological features in cutaneous sebaceous neoplasms--a classification dilemma: report of 5 cases - Kazakov, Dmitry V; Kutzner, Heinz; Spagnolo, Dominic V; Rütten, Arno; Mukensnabl, Petr; Michal, Michal (The American Journal of dermatopathology, 2009)
The authors present a series of 5 cases of cutaneous sebaceous neoplasms having "benign" architectural features (symmetry, sharp circumscription, smooth borders, pseudoencapsulation) but which simultaneously displayed atypical cytology including abnormal mitoses, high mitotic rates, and moderate-to-striking pleomorphism including bizarre cells. The patients included 4 females and 1 male, ranging in age at diagnosis from 49 to 72 years. All presented with a small solitary nodule (6-9 mm) on the forehead (2), chest wall (1), occiput (1), and shoulder (1). The lesions were surgically excised. There were no recurrences on follow-up ranging from 16 to 148 months (average 77 months). In none of the patients was there a history of internal malignancy before or after diagnosis of the cutaneous neoplasms. Of 3 tumors assessed immunohistochemically for the expression of DNA mismatch repair gene proteins, only one showed loss of MLH1 expression. This was the only tumor to contain numerous tumor-infiltrating lymphocytes. Our report emphasizes the existence of rare sebaceous tumors that, despite a deceptively bland architectural appearance, discordantly exhibit a range of atypical cytological features more characteristic of either low-grade or even high-grade carcinomas. Whether such tumors should be classified as sebaceomas with atypia or sebaceous carcinomas is unclear at present. Further studies are needed to confirm their seemingly benign course as identified in this report, as are further investigations to clarify their association with Muir-Torre syndrome.
Keywords: Female; Aged; Humans; ženské pohlaví; mužské pohlaví; senioři; lidé; Male; lidé středního věku; Middle Aged; Sebaceous Gland Neoplasms; Immunohistochemistry; nádory mazových žláz; imunohistochemie